Bayes And Least-Squares Procedures In Sampling From Finite Populations - Mehrotra, Pretta Latha (1984)
In this thesis, we shall consider estimation 1n finite populations under a model-based superpopulation approach using least-squares and Bayesian prediction procedures. Greater emphasis will be placed on the Bayesian inference. The first chapter covers a general preview of the 'classical' fixed population approach and the superpopulation model-based approach, the general survey design framework used and a literature review relevant to this study.